Research on adaptive control of self-moving temporary support based on fuzzy PID - MA Changqing; LI Feng; HUANG Yubo; MAO Junjie; LI Xuyang; WEI Xiangyu; MA Xiaoyang (Gong-kuang zidonghua)
To address the issue of poor adaptability of self-moving temporary supports and roofs during roadway excavation, an adaptive control method of self-moving temporary support based on fuzzy PID was proposed. The working principle of self-moving temporary support was analyzed. A pressure adjustment circuit was added to the control circuit of the support hydraulic cylinder to tackle the problem of adapting to changes in roof pressure, and a self-moving temporary support force control system was established. To enable the self-moving temporary support force (i.e., the output force of the support hydraulic cylinder) to quickly and stably track the expected value, a fuzzy PID adaptive control system model was established to enable online adjustment of PID parameters. This achieved adaptive control of self-moving temporary support, enhancing its adaptability to special working conditions such as roof unevenness and inclination. Simulation models of traditional PID control and fuzzy PID adaptive control systems were built in Matlab/Simulink. The simulation results showed that the fuzzy PID-based adaptive control system demonstrated better tracking performance for the surrounding rock roof pressure compared to traditional PID control.The error of the temporary support adaptive control system following the surrounding rock pressure is 0.004 3, which is 86.11% lower than that of the traditional PID control. The adaptive control system of self-moving temporary support based on fuzzy PID stabilized at 0.12 s, whereas traditional PID control stabilized at 8.685 s, indicating a significant advantage in response speed for the fuzzy PID adaptive control. A displacement control system model of the support hydraulic cylinder was established in AMESim and jointly simulated with Matlab/Simulink. During leveling, data from adjacent support hydraulic cylinders were selected for research and analysis. Results indicated that the synchronization error between adjacent hydraulic cylinders was generally controlled within ±5×10−15 m, showing significant precise improvement over traditional PID control method. The curves exhibited uniform and gentle fluctuations with smaller amplitude fluctuation range.